Development of in vitro models to investigate the anti-inflammatory properties of Cyclopia Maculata and other South African herbal teas : a comparative study - Keet, Lana (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.